IstirÄtÄ«jiyyat QirÄâ€™at Kutub al-Turath â€˜ala AsÄs Naáº“ariyyat Rebecca Oxford fÄ« Taâ€˜allum al-Lughat al-Ajnabiyat - Rizki, Restu Budiansyah (Alsina : Journal of Arabic Studies, 2019)
This study aims to determine the strategies used by superior students and less superior students and then the similarities and differences between each group of students in the use of strategies. This research uses a qualitative descriptive field approach. Data collection method is based on (1) authentication method (2) questionnaire method (3) interview method. Data analysis for this study was based on the Mehlis and Hubermin methods, including four steps: (1) data collection, (2) data reduction, (3) data presentation, and (4) extraction or extraction. Therefore, this study is used to test the validity of data by triangulation by source and triangulation by data collection methods. The results of this study are: (1) The strategies used by superior students are social strategies, supra-cognitive strategies and cognitive strategies, (2) Strategies used in students who are less superior are social strategies, reminding strategies and supra-cognitive strategies. . However, the difference in strategy use is in the memorial strategy, cognitive strategy, supra-cognitive strategy and impact strategy.